2021
DOI: 10.1016/j.sjbs.2020.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pain, psychological-distress, SARS-CoV2 fear on adults’ OHRQOL during COVID-19 pandemic

Abstract: Corona virus disease (COVID-19) has crippled life, families and oral health care delivery. Hence, we assessed the impact of dental pain, fear of COVID-19 and psychological distress during lockdown on the oral health related quality of life of individuals visiting a tertiary dental care center during COVID-19 pandemic. Cross sectional study conducted among patients between 18-60 years. Demographics, access to pain killers, dental care (yes/no), duration ( 15 days) and intensity of pain were self reported. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 12 publications
3
28
0
Order By: Relevance
“…Due to the possibility of comparison with pre-pandemic results, a longitudinal assessment was possible and showed an increase in the PHQ-Stress score of 1.14 ± 0.02, an increase in PHQ-9 by 0.38 ± 0.02 and an increase of the GAD-9 by 0.36 ± 0.02. 24 Samuel et al presented similar results, as higher values of the Fear of COVID-19 scale suggest a reduced OHRQoL 25 .…”
Section: Discussionmentioning
confidence: 75%
“…Due to the possibility of comparison with pre-pandemic results, a longitudinal assessment was possible and showed an increase in the PHQ-Stress score of 1.14 ± 0.02, an increase in PHQ-9 by 0.38 ± 0.02 and an increase of the GAD-9 by 0.36 ± 0.02. 24 Samuel et al presented similar results, as higher values of the Fear of COVID-19 scale suggest a reduced OHRQoL 25 .…”
Section: Discussionmentioning
confidence: 75%
“…To the best of our knowledge, the present study is the first to report the economic impact of the COVID-19 pandemic on dental health outcomes. Although previous studies have reported the characteristics of patients who visited emergency dental care during the national lockdown (Bai et al 2020; Samuel et al 2021) and infection control in dental clinics to reduce person-to-person transmission (Zemouri et al 2020), the impact of COVID-19 on dental health has not been evaluated. A study from Chennai, India, reported that dental pain, fear of COVID-19, and psychological distress were associated with low oral health–related quality of life (OHRQOL) (Samuel et al 2021); they failed to compare people with and without dental symptoms as the study participants were patients who visited a dental institute for emergency care.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have reported the characteristics of patients who visited emergency dental care during the national lockdown (Bai et al 2020; Samuel et al 2021) and infection control in dental clinics to reduce person-to-person transmission (Zemouri et al 2020), the impact of COVID-19 on dental health has not been evaluated. A study from Chennai, India, reported that dental pain, fear of COVID-19, and psychological distress were associated with low oral health–related quality of life (OHRQOL) (Samuel et al 2021); they failed to compare people with and without dental symptoms as the study participants were patients who visited a dental institute for emergency care. Although few studies are directly comparable to ours, the findings are supported by a previous study conducted following another crisis, the devastating 2011 earthquake in Japan, showing that survivors who had lost their properties were more likely to report dental pain (Tsuchiya et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Months after reopening the dental offices, studies showed that the probability of COVID-19 contamination within dental clinics was very low [ 15 ]. On the other hand, dental patients were underserved both because they were forced to interrupt their treatments during the lockdown and to access only dental emergency treatments for acute issues and they had to postpone their dental treatment [ 16 , 17 , 18 ]. Moreover, some of them were afraid to attend the dental check-ups because of their fear for COVID-19 contamination [ 16 ]; therefore, they cancelled the regular dental visits, thus increasing the risk for developing new oral health issues or relapse.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, dental patients were underserved both because they were forced to interrupt their treatments during the lockdown and to access only dental emergency treatments for acute issues and they had to postpone their dental treatment [ 16 , 17 , 18 ]. Moreover, some of them were afraid to attend the dental check-ups because of their fear for COVID-19 contamination [ 16 ]; therefore, they cancelled the regular dental visits, thus increasing the risk for developing new oral health issues or relapse. In addition, recently published research [ 19 ] showed that periodontal disease, as chronic inflammatory disease, increases the risk for Intensive Care Unit attendance and even death among patients with COVID-19 infection, since any chronic inflammatory disease contributes to the amplification of complications and negative prognosis of this COVID-19-induced infection [ 20 ].…”
Section: Introductionmentioning
confidence: 99%